Synthesis of 1',2',3',4'-tetrahydro-1,1'-biisoquinoline derivatives and the application in the aldol reaction - Juniwati, Fitri. (2010)
The possibility of catalyzing asymmetric reaction without the use of metal complex, but with purely organic compounds has gained much attention recently. The term “organocatalysts” was thus coined out to describe this new field of the organic chemistry. An example of the organocatalysts is (S)-proline, a widely available amino acid, which was found to be an extremely effective catalyst for the aldol reaction, affording excellent enantioselectivities. The drive to explore alternative potential organocatalysts other than (S)-proline provided the motivation to explore efficiency of 1’,2’,3’,4’-tetrahydro-1,1’-biisoquinoline (BIQ) and its derivatives in the asymmetric aldol reaction.